Active Conflict and Access to Education : Evidence from a Series of Conflict-Related Shocks in the Republic of Yemen - Almoayad, Safa; Favari, Eliana; Halabi, Samira; Krishnaswamy, Siddharth; Music, Almedina; Tandon, Sharad (World Bank, Washington, DC, 2020)
Using a high-frequency survey in the Republic of Yemen, this paper demonstrates how school attendance responds to a series of conflict-related shocks. First, there are plausibly exogenous changes in violence that have limited impacts on school attendance but do affect other dimensions of well-being. And second, consequences of conflict aside from living in close proximity to violence can impact attendance. The importance of a wide variety of conflict shocks suggests that an understanding of all shocks is needed before attributing the cause of attendance changes in such tumultuous settings, and these results have implications for the delivery of education assistance in conflict settings.